How do environmental and cultural factors shape red tourism behavioral intentions: a moderated mediation model - Cong Chen; Cong Chen; Yinghui Lai; Chenjing Huo (Frontiers in Psychology)
IntroductionThis study investigates how environmental restorativeness perception and cultural identity shape the relationship between red tourism experience and post-visit behavioral intentions.MethodsA structured questionnaire was administered to 1,195 tourists at two iconic red tourism destinations in China, Xibaipo and Shaoshan. Key constructs, including red tourism experience, environmental restorativeness perception, cultural identity, and post-visit behavioral intentions, were assessed using validated multi-item scales. After controlling for gender, age, and education as covariates, latent moderated structural equation modeling (LMS) was employed to analyze mediation and moderation effects.ResultsThe results indicate that environmental restorativeness perception significantly mediates the influence of red tourism experience on post-visit behavioral intentions. Cultural identity significantly moderates the first stage of this mediation pathway, such that higher cultural identity strengthens the positive effect of red tourism experience on perceived restorativeness.DiscussionThese findings suggest that red tourism environments can restore attention and reduce stress while simultaneously reinforcing collective identity, thus promoting loyalty behaviors. The study contributes to environmental psychology and heritage tourism by highlighting the dual pathway through which ideological landscapes foster both emotional recovery and socio-cultural engagement.